Gaya Busana Raja Dinasti Syailendra Sebagai Sumber Pembelajaran Digital - Kiemas, Muhammad Hikmal Akbar; Idris, Muhammad; Zamhari, Ahmad (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This article aims to find out the clothing style of the kings of the Syailendra Dynasty as a digital history learning source. This is important because you need to know King Syailendra’s fashion style. The method used in the research is the qualitative descriptive method. With data collection techniques in the form of observation, interviews. Data analysis techniques are used to identify statues related to the Syailendra dynasty. The results of the research show that the fashion style of the kings of the Syailendra dynasty can be used as a digital learning resource, namely to increase students’ understanding.